A case of septicaemic pasteurellosis in captive sambar deer, cervus unicolor - Wan Norulhuda W. A. W. (2020)
Septicaemic pasteurellosis is a fatal, sometimes epidemic, bacterial disease of domestic and wild animals including deer, bison, elk, and pronghorn antelope caused by Pasteurella multocida. This is the case report of septicaemic pasteurellosis in a captive sambar deer. The carcass was sent from Royal Endurance Stable, Bachok, Kelantan to the Kota Bharu Regional Veterinary Laboratory for post-mortem. Gross examination of organs was followed by collection of specimens from lung, kidney, liver, spleen and heart for histopathology and bacterial examination. Pooled organ samples with rumen content were collected and sent to the nearest Chemistry Department for investigation. For histology, the liver, lung, spleen, kidney, and heart specimens were fixed in 10% neutral formalin, and routinely embedded in paraffin. Fivemicrometer sections were stained with H&E. Other tests such as worm and ectoparasite identification were conducted to identify the parasites. Post-mortem lesions revealed generalised haemorrhage in the organs. Pasteurella multocida serogroup B and E. coli were isolated from multiple tissues of the animal. Histological examination also revealed severe congestion and haemorhage of multiple tissues with infiltration of the inflammatory cells. The most likely mode of transmission of these bacteria is through an infected wound and into the bloodstream, thereby causing severe septicemia and death to the animal.